Demystifying the stigma in the writings of carolina maria de jesus: Translation strategies in translating “favela” - Claúdia Suriani da Silva, Ana; Uliana, Elton; Andréa Fernandez, Raffaella (Revista Linguagem & Ensino, 2022)
This article discusses the process of translating Carolina Maria de Jesus’s autobiographical narrative “Favela”, published in Onde estaes felicidade? in 2014, a translation project carried out as an experiment within the SELCS Brazilian Translation Club workshops in October 2021 at University College London. The study identifies points of convergence within the translation, and divergences from expected English cultural and linguistic norms, as well as detailed analyses of several strategies for dealing with problems and concepts such as equivalence, foreignisation, acculturation, and untranslatability. The reflection on translation procedures was guided by the principle of “negative revision”, taking into account the most recent research on the teaching and the practice of literary translation, and paying particular attention to Carolina Maria de Jesus’ autographs, which in themselves dispel several racial, social and cultural stigmas conveyed by the first editions and translations of the author’s work.